Effects of Lavender Aromatherapy on Students' Anxiety during Emergency Maternal and Neonatal Final Exams - Mutmainnah; St. Malka (Comprehensive Health Care, 2025)
Anxiety in students is usually something that is considered threatening such as the implementation of the final semester exam (UAS). Approaching the UAS schedule, students begin to feel restless, especially in compulsory courses. Anxiety affects several organs such as visceral and motoric, as well as thoughts, perception, and learning. Therefore, anxiety can inhibit cognitive function which affects performance during exams. Complementary medicine is currently becoming a hype, because of a paradigm shift, namely treatment that prioritizes non-pharmacological therapy, to reduce the side effects of chemical drugs. Effects of Lavender Aromatherapy on Students' Anxiety during Emergency Maternal and Neonatal Assessments The study's goal was to examine the impact of using lavender aromatherapy on students' anxiety during the maternal and neonatal emergency health examination. Research method with a single group pre-test and post-test design, the research is a quasi-experiment. There were 38 students in the research sample who met the inclusion criteria.The results of the Wilcoxon p-value test analysis 0.000 means ppparently students' anxiety levels before the maternity and neonatal emergency health exam are affected by the use of lavender aromatherapy. According to the study's findings, students' anxiety levels before final exams can be decreased by using lavender aromatherapy.